THE EFFECT OF KETAPANG (Terminalia catappa) LEAF EXTRACT DOSAGE ON THE SURVIVAL RATE OF 5–7 CM STRIPED CATFISH (Pangasius pangasius) FINGERLINGS INFECTED WITH Edwardsiella tarda - Laili Rohmah; Muhajir Muhajir; Achmad Kusyairi (Universitas Mataram, 2026)
Pangasius cultivation is an important aquaculture sector in Indonesia. However, intensification programs are often accompanied by increased vulnerability to disease. One disease that frequently occurs in pangasius cultivation is the systemic bacterial disease Motile Edwardsiella Septicemia (MES), also known as Edwardsiellosis. This disease is caused by infection with the bacterium Edwardsiella tarda and causes mortality of 5-7 cm pangasius fry ranging from 80-95% for 2-8 weeks. Treating fish diseases using chemicals can trigger new problems, such as antibiotic residues, bacterial resistance, and environmental pollution. A widely developed strategy utilizes herbal ingredients as immunostimulants and antibacterial agents, one of which is extract of ketapang (Terminalia catappa) leaves. This study aims to determine the effect of the dose of ketapang leaf extract on the survival rate of 5-7 cm pangasius fry infected with Edwardsiella tarda bacteria. This study used an experimental method with a Completely Randomized Design (CRD) consisting of 5 treatments and 5 replications. This study used different doses of ketapang leaf extract. Treatment A; Ketapang leaf extract dose of 100 mg/L, Treatment B; Ketapang leaf extract dose of 200 mg/L, Treatment C; Ketapang leaf extract dose of 300 mg/L, Treatment D; Ketapang leaf extract dose of 400 mg/L, Treatment E; Ketapang leaf extract dose of 500 mg/L. The test animals used catfish seeds measuring 5-7 cm with an average weight of 3.5 g/tail. The stocking density was 3 tails/L, the experimental media used fresh water with a volume of 3 L/container. The results showed that treatment C gave the best results on the survival rate of 5-7 cm catfish seeds of 93.33%.